(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2017)
When asked to write an introduction for one of the chapters in Community Engagement: A Critical Guide for Practioners it was the first chapter on ‘Thinking Politically’ that leapt out at me. Sometimes in the field of practice it can be easy to get caught up in having to react, often quickly, to the complex and contradictory forces that are at play within community education. Chapter One brought me back to key fundamental but political questions and issues in relation to Community Engagement that one should never lose sight of such as what is its purpose plus why and what is it funded for? As practitioners, it’s important to take time to draw on theoretical ideas and concepts in order to make some kind of sense of the dynamics and tensions that can exist between policies, politics, power, the people we work with and their lived experience, plus our own values and stances as workers.